Regarding the Forms of Criminal-legal Reaction of the State: Modern Trends - Стрельцов, Євген Львович; Стрельцов, Є. Л.; Стрельцов, Евгений Львович; Streltsov, Yevhen L.; Streltsov, Yevgen (My University, 2024)
The development of social processes, which is always inherent in social progress, at certain times acquires, generally speaking, a certain dynamism and even hyperdynamism, which is also, to a certain extent, characteristic of modern times. Certainly, these are different processes in many of their indicators, and this fact, in turn, gives rise to a number of objective difficulties in terms of understanding such processes, their interpretation, development of measures, forms and types of state reaction to them. This also concerns problems that occur in the legal plane at the general and sectoral levels. Doctor of Law, Doctor of Theology, Professor, Corresponding Member of the National Academy of Legal Sciences of Ukraine, Honored Scientific Worker of Ukraine Yevgen L. Streltsov shares his thoughts on the complex problems of applying criminal-legal measures in modern conditions. Considering that he’s been currently working as a researcher at the Institute of East European Law (Regensburg, Germany) as a DAAD fellow, his reflections are supplemented by a comparative analysis of the forementioned issues.
Streltsov Y. Regarding the Forms of Criminal-legal Reaction of the State: Modern Trends / Yevgen L. Streltsov // Ukrainian National weekly Legal Herald of Ukraine (NW “LHU”). – 2024. – 1-15 September (№ 35/36). – С. 20-24 ; 16-30 September (№ 37/38). – С. 20-23 ; 1 – 15 October (№ 39/40). – С. 20-22.
Keywords: goals and tasks of criminal law; criminal law science; criminal law; criminal legislation; crime; criminal offense in Ukraine; criminal punishment; economic criminal offenses; property penalties; Institute for East European Law (IOR)